Involuntary movements : classification and video atlas - Shibasaki, Hiroshi, 1939-; Hallett, Mark, 1943-; Bhatia, Kailash; Reich, Stephen G.; Balint, Bettina (New York, NY : Oxford University Press, 2020)
'Involuntary Movements' pairs descriptions of the clinical features of various involuntary movements with video depictions of the involuntary movements in action. In a unique approach, this work considers two aspects of the diagnosis of involuntary movements: the phenomenology - as depicted in approximately 200 video supplements - and the etiology. The text also discusses the current consensus on the classification, pathophysiology, and treatment of each.
Also issued in print: 2020.
Includes video clips.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 17, 2020).
Keywords: Movement disorders